"My Uni Experience Wasn't Completely Ruined" : The Impacts of COVID-19 on the First-Year Experience. - McKay, Loraine; O'Bryan, Steven; Kahu, Ella R. (Student Success v.12 n.3 p.1-13 https://doi.org/10.5204/ssj.1762, 2021)
The first year at university is always challenging, but particularly in 2020 when COVID-19 triggered lockdowns and a rapid shift to online learning. This mixed methods study tracked the wellbeing and engagement of 60 new students in an undergraduate teacher education program at an Australian university throughout the first trimester of 2020. Follow-up focus groups with 14 students used interview and photo elicitation to explore how COVID-19 influenced wellbeing and engagement. Quantitative results demonstrate both student wellbeing and student engagement dipped strongly at the start of lockdown but recovered towards the end of the trimester. Focus group findings illustrate the diversity of experience in terms of student access to time and space to study, their ability to sustain relationships online, and the cumulative stress of COVID-19. The findings lead to recommendations for supporting this cohort and for future research. [Author abstract]